The Application of Metaphor Identification Procedure and Conceptual Metaphor Theory in Persian and Malay Languages - Safarnejad, Fatemeh; Ghani, Aniswal ABD. (LANGUAGE ART, 2019)
Metaphor is a linguistic element that can be found in different languages. The scope of the present study is restricted to the metaphorical expressions of only the two concepts of Happiness and Sadness as presented in Persian and Malay languages. The study uses Metaphor Identification Procedure (MIP) and the Conceptual Metaphor Theory (CMT) framework. In this study, two sets of data (Persian and Malay linguistic data) were examined. The Persian linguistic data were collected from the Persian novel “Suvashun” written by Simin Daneshvar. The Malay linguistic data were gathered from the Malay novels written by Wan Osman Wan Awang. These emotive metaphorical expressions were compared to assess whether they were identical, similar or different. The analysis of data showed that emotive metaphorical expressions of Happiness and Sadness are characterized by cognitive commonness and cultural variety. The findings show that the two languages have many metaphorical expressions of Happiness/Sadness that are based on common bodily experiences. Furthermore, the analysis of metaphorical expressions of Happiness and Sadness in the two languages showed that the metaphor is quite pervasive in expressions of emotional concepts, and it plays an essential role in our understanding and speaking. The results of this study suggest that the application of Metaphor Identification Procedure (MIP) offers a reliable and flexible method for identifying metaphorical expressions at the linguistic level, and the Conceptual Metaphor Theory (CMT) provides a systematic instrument to identify the concepts of emotive metaphorical expressions behind the linguistic metaphors.